SCHOOL ACCREDITATION SYSTEM: DEFINITION OF ACCREDITATION, BASIS FOR IMPLEMENTATION, AND SCOPE - Muhammad Ridho; Faisal; Husnul Yaqin; Hilmi Mizani (Review of International Journal Education and School Leadership, 2026)
This research critically examines the conceptualization of school accreditation, the legal foundations of its implementation, and its scope within the context of national education governance, with a focus on analyzing the role of the National Accreditation Board for Schools and Madrasahs as an independent evaluative body under the coordination of the Ministry of Education, Culture, Research, and Technology. Adopting a qualitative paradigm through a systematic literature review design, this research analyzes a corpus of regulatory documents, particularly Law No. 20 of 2003 along with related regulations on National Education Standards, as well as a curated synthesis of scientific literature from reputable journals and academic publications. The findings indicate that accreditation operates on multiple levels: in addition to serving as an instrument of external verification across the eight domains of educational standards (graduate competencies, curriculum content, teaching practices, educator resources, infrastructure, institutional management, funding allocation, and assessment systems), this practice also functions as a mechanism for continuous quality improvement within the school ecosystem. Therefore, the integrity of the accreditation process—which prioritizes objectivity and transparency—is a fundamental prerequisite for maintaining public accountability and enhancing stakeholders’ trust in quality educational services.